The Correlation between Students’ Reading Motivation and Reading Comprehension at Eighth Grade Students Level - Radiyah Radiyah; Annisa Astrid; Husnaini Husnaini (Jurnal Educatio FKIP UNMA, 2023)
The purposes of this research were to find out: (1) there was a correlation between students’ reading motivation and reading comprehension of students at eighth grade level in Palembang, (2) How much motivation contributed to reading comprehension of students at eighth grade level in Palembang. The population of this research was three private schools in Palembang (SMP Islam Az-Zahrah 1 Palembang, SMP IT Harapan Mulia Palembang, and SMP Tarbiyah Palembang) which consisted of two hundred ten students. And then, one hundred ten students were selected as the sample using the convenience sampling technique. The data were collected by using MRQ questionnaire by Wang and Guthrie (2004) and a reading comprehension test. Pearson Product Moment and regression analysis were used to determine the correlation and the contribution between the two variables. The result showed a correlation between reading motivation and reading comprehension with r (.257). Besides, there was also the contribution of reading motivation and reading comprehension with 6,6%. This research could have implications for English teachers, students, and subsequent researchers.